Adjusting for treatment switching in the METRIC study shows further improved overall survival with trametinib compared with chemotherapy. (27th January 2016) - Latimer, Nicholas R.; Bell, Helen; Abrams, Keith R.; Amonkar, Mayur M.; Casey, Michelle
Abstract: Trametinib, a selective inhibitor of mitogen‐activated protein kinase kinase 1 (MEK1) and MEK2, significantly improves progression‐free survival compared with chemotherapy in patients with BRAF V600E/K mutation–positive advanced or metastatic melanoma (MM). However, the pivotal clinical trial permitted randomized chemotherapy control group patients to switch to trametinib after disease progression, which confounded estimates of the overall survival (OS) advantage of trametinib. Our purpose was to estimate the switching‐adjusted treatment effect of trametinib for OS and assess the suitability of each adjustment method in the primary efficacy population. Of the patients randomized to chemotherapy, 67.4% switched to trametinib. We applied the rank‐preserving structural failure time model, inverse probability of censoring weights, and a two‐stage accelerated failure time model to obtain estimates of the relative treatment effect adjusted for switching. The intent‐to‐treat (ITT) analysis estimated a 28% reduction in the hazard of death with trametinib treatment (hazard ratio [HR], 0.72; 95% CI, 0.52–0.98) for patients in the primary efficacy population (data cut May 20, 2013). Adjustment analyses deemed plausible provided OS HR point estimates ranging from 0.48 to 0.53. Similar reductions in the HR were estimated for the first‐line metastatic subgroup. Treatment with trametinib, compared with chemotherapy, significantly reduced the risk of death and risk of disease progression in patients with BRAF V600E/K mutation–positive advanced melanoma or MM. Adjusting for switching resulted in lower HRs than those obtained from standard ITT analyses. However, CI are wide and results are sensitive to the assumptions associated with each adjustment method. Abstract : Survival analyses for the pivotal METRIC trial in metastatic melanoma were confounded by patients switching treatment from the chemotherapy control arm to the trametinib arm after disease progression. Adjusting for treatment switching lowered the hazard ratio for risk of death compared to results from the standard intent‐to‐treat analysis; however, adjusted results are sensitive to assumptions associated with adjustment methods.